2002
DOI: 10.1046/j.1523-1755.2002.00413.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of feeding on albumin synthesis in hypoalbuminemic hemodialysis patients

Abstract: There are differences of body composition and protein metabolism in HHD patients that may be related to an impaired metabolic response to feeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 21 publications
3
4
0
Order By: Relevance
“…Aoyagi et al [16] in literature review report other studies' results showing systematic weight loss in patients chronically dialysed for 10-15 years. Different results, but confirming the results of this study, were reported by Louden et al [17]. They showed that proper intake of energy and protein in the group of dialysed patients can reduce the loss of body weight and even contribute to the increase in BMI value.…”
Section: Resultssupporting
confidence: 92%
“…Aoyagi et al [16] in literature review report other studies' results showing systematic weight loss in patients chronically dialysed for 10-15 years. Different results, but confirming the results of this study, were reported by Louden et al [17]. They showed that proper intake of energy and protein in the group of dialysed patients can reduce the loss of body weight and even contribute to the increase in BMI value.…”
Section: Resultssupporting
confidence: 92%
“…The albumin FSR results reported in the current study are quantitatively comparable with findings from other studies. Louden et al (16) reported a similar albumin FSR during the PA (12.9 ± 0.6%/d) and PP states (15.2 ± 0.6%/d) using [1-13 C] leucine in healthy adults aged 52 ± 3 y. Barber et al (17) also reported a similar differential response of albumin FSR between the PA (5.5-14.8%/d) and the PP states (11.0-15.7%/d) in healthy adults (aged 50-62 y).…”
Section: Discussionmentioning
confidence: 99%
“…In the current study the smaller differential response of albumin FSR from PA to PP state with decreasing dietary protein intake from above the RDA (P125) to protein intake below the RDA (P94 and P63) was a likely response because of the smaller amino acid substrate available for protein synthesis. Other researchers have not tested this proteinrelated response to meal consumption, but have reported an increase in albumin protein synthesis during the PP state compared with the PA state (15)(16)(17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Infl ammation is the principal cause of decreased serum albumin, protein intake has an insignifi cant role [1]. There is a high prevalence of infl ammation and oxidative stress in the maintenance hemodialysis population, and infl ammation is a contributor to the hypoalbuminemia in patients on chronic dialysis [20][21][22][23][24][25][26][27]. Many studies demonstrated that the proinfl ammatory cytokines such as TNF-α IL-1β and IL-6 can cause the liver to produce the positive acute phase proteins associated with a decrease in the negative acute phase protein (such as albumin).…”
Section: Discussionmentioning
confidence: 99%